Extent of inappropriate prescription of artemisinin and anti-malarial injections to febrile outpatients, a cross-sectional analytic survey in the Greater Accra region, Ghana - Bonful, Harriet Affran (Malar J, 2019)
BACKGROUND: Febrile children seen in malaria hypo-endemic settings, such as the Greater Accra region (GAR) of Ghana are more likely to be suffering from a non-malarial febrile illness compared to those seen in hyper-endemic settings. The need for prescribers to rely on malaria test results to guide treatment practices in the GAR is even greater. This study was designed to investigate the factors associated with inappropriate artemisinin-based combination therapy (ACT) prescription. METHODS: A survey was conducted in six health facilities in the region in 2015. Treatment practices for febrile outpatient department (OPD) patients were obtained from their records. Prescribers were interviewed and availability of malaria commodities were assessed. The primary outcome was the proportion of patients prescribed ACT inappropriately. Independent variables included patient age and access to care, prescriber factors (professional category, work experience, access to guidelines, exposure to training). Data were analysed using Stata at 95% CI (α-value of 0.05). Frequencies and means were used to describe the characteristics of patients and prescribers. To identify the predictors of inappropriate ACT prescription, regression analyses were performed accounting for clustering. RESULTS: Overall, 2519 febrile OPD records were analysed; 45.6% (n = 1149) were younger than 5 years. Only 40.0% of patients were tested. The proportion of patients who were prescribed ACT inappropriately was 76.4% (n = 791 of 1036). Of these 791 patients, 141 (17.8%) were prescribed anti-malarial injections. Patients seen in facilities with rapid diagnostic tests (RDT) in stock were less likely to be prescribed ACT inappropriately, (AOR: 0.04, 95% CI 0.01–0.14, p < 0.001) compared to those seen in facilities with RDT stock-outs. Prescribers who had been trained on malaria case management within the past year were 4 times more likely to prescribe ACT inappropriately compared to those who had not been trained (AOR: 4.1; 95% CI (1.5–11.6); p < 0.01). Patients seen by prescribers who had been supervised were 8 times more likely to be  prescribed ACT inappropriately. CONCLUSION: Inappropriate ACT prescription to OPD febrile cases was high. Training and supervision of health workers appears not to be yielding the desired outcomes. Further research is needed to understand this observation.